The bad boy of Redemption Ranch - Yates, Maisey (Yates, Maisey. Gold Valley novel., 2020)
Police officer Pansy Daniels is the poster girl for responsible behavior. Orphaned as a child, she has dedicated her life to safeguarding her local community. The last thing she needs is a hot-headed cowboy with attitude cruising into town. He may be her new landlord, but that's no excuse for provoking her ... or sending her heart into overdrive. West Caldwell has come to Redemption Ranch to put his past behind him. Flirting with a pint-size police officer who thinks he's bad news is definitely not part of the plan, but it's deliciously easy to get under Pansy's skin. Then West discovers the vulnerability Pansy keeps so well hidden, and suddenly this renegade cowboy is in over his head. In her arms, West feels like the man he always wanted to be--but can he become the man Pansy deserves?